1998
DOI: 10.1109/78.668546
|View full text |Cite
|
Sign up to set email alerts
|

Theory and design of signal-adapted FIR paraunitary filter banks

Abstract: We study the design of signal{adapted FIR paraunitary lter banks, using energy compaction as the adaptation criterion. We present some important properties that globally optimal solutions to this optimization problem satisfy. In particular, we show that the optimal lters in the rst channel of the lter bank are spectral factors of the solution to a linear semi{in nite programming (SIP) problem. The remaining lters are related to the rst through a matrix eigenvector decomposition. We discuss uniqueness and sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
60
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 10 publications
0
60
0
Order By: Relevance
“…They are useful for designing perfect-reconstruction filter banks in coding and image processing tasks [1][2][3][4][5][6][7] as well as for determining the eigenstructure of multichannel time series in direction-of-arrival estimation and wideband array processing tasks [8][9][10][11][12]. When m = n = 1, (4) guarantees that the single-input, single-output linear system W [z] is an all-pass filter, and thus solutions to (1)-(4) are useful for single-channel deconvolution, equalization, and adaptive control tasks [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are useful for designing perfect-reconstruction filter banks in coding and image processing tasks [1][2][3][4][5][6][7] as well as for determining the eigenstructure of multichannel time series in direction-of-arrival estimation and wideband array processing tasks [8][9][10][11][12]. When m = n = 1, (4) guarantees that the single-input, single-output linear system W [z] is an all-pass filter, and thus solutions to (1)-(4) are useful for single-channel deconvolution, equalization, and adaptive control tasks [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Works in FIR perfect reconstruction filter bank design have largely focused on constructive methods using classic mean-square or least-squares approximation theory with constraints [3][4][5][6]. Realizations of paraunitary systems have largely been parametric or intrinsic parametrizations that employ lattice parameterizations in a linear or tree-based structure [7,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…As such, much attention in the signal processing community has focused on the design of FIR compaction filters [4,3,6]. In [4], the authors proposed a linear semi-infinite programming (SIP) method for the design of such filters.…”
Section: Introductionmentioning
confidence: 99%
“…For both methods, suboptimal numerical techniques were employed. Despite this, in [4], it was shown that for the multiresolution criterion under consideration, the design problem could be greatly simplified since the entire filter bank could be constructed by designing a single FIR compaction filter, followed by an appropriate Karhunen-Loève transform (KLT).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation